Anesthesia Management in Thyroid Tumors - Suhety, Indah (CV. Devitara, 2024)
Thyroid nodules as discrete lesions within the thyroid gland. Nodules in the thyroid gland are detected in approximately 5% to 7% of the adult population by physical examination alone. Thyroid nodules are approximately 4 times more common in women than men Thyroid nodules can be classified as neoplastic and non-neoplastic. The initial evaluation of a patient with a thyroid nodule should include a history, physical examination, thyroid stimulating hormone (TSH) measurement, and thyroid ultrasonography to characterize the nodule. TSH measurement by itself may detect subtle thyroid dysfunction. Diagnostic tests include serum markers, fine needle aspiration (FNA) cytology, genetic markers, immunohistochemical markers, and several imaging modalities, most commonly ultrasonography, but also elastography, MRI, CT, and 18FDG-PET scanning. Thyroidectomy is the most common endocrine surgery. Due to compression on the trachea, airway management can be difficult.[1] Preoperative evaluation and management are critical when planning elective thyroidectomy, where changes in the anatomical location are expected because of a large or substernal goiter. Anatomical changes, laryngeal edema and an inexperienced team can all contribute to difficulty in intubation. The incidence of difficult tracheal intubation (DTI) in the patient population undergoing thyroid surgery varies. Several studies found a similar value for the incidence of DTI (5.3% to 6.8%). Previous studies have evaluated risk factors for DTI in patients undergoing thyroid surgery. Increasing age, high Mallampati score, Grade III or IV Cormack score, reduced mouth opening (<4.4 cm), goiter cancer and tracheal stenosis (≥30%) are independent predictors of DTI. Neck circumference (NC) appears to be an important predictor of DTI.